DIVERSITY AND DISTRIBUTION OF BENTHIC MACROINVERTEBRATE FAUNA OF NASARAWA RESERVOIR IN JIBIA, KATSINA STATE NIGERIA - Zahraddeen, H. Y.; Babangida, A.; Isiyaku, I. I. (FUDMA Journal of Sciences, 2023)
A study was conducted for a period of 10 months from February to November, 2018 to evaluate the macroinvertebrate structure, abundance, distribution and diversity of benthic fauna of Nasarawa reservoir, Jibia, Katsina State. The benthic fauna were collected using Identification guide to freshwater macroinvertebrates manual on monthly basis from 5 sampling sites. A total of 4460 macrobenthic invertebrates comprising 3 phyla, 3 classes, 6 families and 17 species were recorded. Overall macrobenthic population at the different stations revealed that the study area was dominated by Mollusca (41.18%), Oligochaetae (23.53.56%), Coleoptera and Diptera (11.77%), Ephemerophtera and Odonata (5.89%). More macrobenthic invertebrate were recorded in the dry season than in the wet season. Simpson (1-D), Shannon (H) and evenness were higher during the dry season than in the wet season but dominance was higher in the wet season. Mollusca were the most dominant taxa recorded during the study period. Species richness as revealed by the Margaleff and Menhinick index was higher during the wet season than in the dry season. The variations in taxa and number of individuals during the months of sampling was not significantly different (P>0.05). Nature of the water body, habitat richness and stability, immediate substrate of occupation, tropic condition, resource partitioning and predation are factors that are likely to influence diversity and distribution of benthic macroinvertebrate fauna of Nasarawa reservoir